MACMEO: Playable Framework for Analog, Hybrid and Digital Serious Game Design - Micael Sousa (International Journal of Serious Games)
Practical tools to support newcomers to serious game design are scarce. We propose the MACMEO framework, developed as a research design process during several sessions, as a flexible and adaptable gamified analog toolkit to help design analog, hybrid or digital serious games through a structured process. The framework can be applied in faster or longer sessions, requiring minimal resources but demanding facilitation when dealing with less experienced users.